Latent profile analysis and influence factors study of nurses’ job performance - Liu, Zhenfan; Yan, Xiaoting; Xie, Guifang; Lu, Jing; Wang, Zhitong; Chen, Cui; Wu, Jijun; Qing, Wei (Frontiers in Psychology, 2025)
ObjectiveTo investigate the current status of nurses’ job performance, to analyze the latent profile analysis of nurses’ job performance and their relationship with occupational coping self-efficacy, perceived social support and to explore the factors influencing the different profiles.MethodsFrom April to June 2024, 390 nurses from five general hospitals were facilitated to be selected as survey respondents using a general information questionnaire, job performance scale, occupational coping self-efficacy scale, and perceived social support scale. Latent profile analysis of nurses’ job performance were analyzed, and logistic regression was used to analyze the factors influencing different categories of nurses’ job performance.Results390 nurses were finally included. Nurses job performance score was (45.05 ± 6.55). Nurses’ job performance could be categorized into three latent profile analysis: low job performance (13.9%), medium job performance (52.8%) and high job performance (33.3%). Logistic regression analysis showed that years of working experience, form of employment, perceived social support and occupational coping self-efficacy were the influencing factors of nurses’ job performance (all p < 0.05).ConclusionNurses’ job performance is moderate to high and heterogeneous. Nursing managers should focus on “low job performance” and “medium job performance” nurses, and intervene and support nurses according to the characteristics and influencing factors of the different categories in order to improve their performance.